Vitamin D3 supplementation improves testicular function in diabetic rats through peroxisome proliferator‐activated receptor‐γ/transforming growth factor‐beta 1/nuclear factor‐kappa B. Issue 2 (6th August 2018) - Liu, Yang; He, Yanyan; Wang, Qingzhu; Guo, Feng; Huang, Fengjuan; Ji, Linlin; An, Tingting; Qin, Guijun
Abstract: Aims/Introduction: Vitamin D3 deficiency can lead to male hypogonadism in diabetes mellitus, but the target organs and the mechanism driving the disorder are unclear. This experiment was designed to study the relationship between vitamin D3 deficiency and hypogonadism in diabetes mellitus. Materials and Methods: Rats with streptozotocin‐induced diabetes were randomly divided into four groups and treated with different doses of vitamin D3 : blank (no vitamin D3 ), low (0.025 μg/kg/day), high (0.1 μg/kg/day), high (0.1 μg/kg/day) and with bisphenol A diglycidyl ether (peroxisome proliferator‐activated receptor gamma inhibitor 30 mg/kg/day). They were compared with wild‐type rats. Results: After 12 weeks, the vitamin D3 supplements had partially restored testicular pathological changes, as shown by reduced testicular fibrosis related to downregulation transforming growth factor beta 1 and apoptosis related to downregulation of nuclear factor kappa B, but not the pituitary gland. The expression of peroxisome proliferator‐activated receptor gamma, which can inhibit transforming growth factor beta 1 and nuclear factor kappa B, was significantly increased after treatment with vitamin D3 . Conclusions: These results suggest that treatment with vitamin D3 can improve testicular function in diabetic rats through the peroxisome proliferator‐activated receptor gamma/transforming growth factor beta 1/nuclear factor kappa B signaling pathway. Abstract : In this study, we assessed the effects of vitamin D3 on the testicular function of diabetic rats. We found that vitamin D3 acted on the testes, but not the pituitary, via the PPAR‐γ/TGF‐β1/NF‐κB signaling pathway.